An online marketing strategies assessment for companies in airlines and entertainment industries in Malaysia - Robert Jeyakumar Nathan; Fook, Desmond Chiun Chong; Norazah Mohd Suki (2016)
In promoting tourism, businesses in entertainment industry should provide e-commerce to their potential customers. Amongst the businesses in entertainment that are engaged in e-commerce include Sunway Lagoon, Golden Screen Cinemas (GSC), Escape-Room and KidZania. Hence, this chapter presents an evaluation of online marketing strategies and tools used by airlines industries like Malaysia Airlines System (MAS), Firefly, AirAsia, and Malindo Air, besides entertainment industries such as Sunway Lagoon, Golden Screen Cinemas (GSC), Escape-Room and KidZania. This research noted that websites need to be more interactive, enable customers to interact and socialize among each other through membership management and additional value-added information. Website with graphics and hyperlinks are not persuasive enough, website should improve with additional suggestions or 'show more' features to invite customer perform additional clicks and explore to the website. Most of the website offers membership to its customer. This, this membership function should be fully utilized.